Thermodynamic properties of the liquid Hg-Tl alloys determined from vapour pressure measurements - Gierlotka W.; Fitzner K.; Sukiennik M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The partial vapour pressure of mercury over liquid Hg-Tl liquid solutions were determined in the temperature range from 450 to 700 K by direct vapour pressure measurements carried out with the quartz gauge. From the measured ln pHg vs. T relationships activities of mercury were determined. Using Redlich-Kister formulas logarithms of the activity coefficients were described with the following equations: From which all thermodynamic functions in the solutions can be derived.